2015
DOI: 10.1007/s00192-015-2894-3
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant apical suspensory procedures in women with anterior vaginal wall prolapse in the United States in 2011

Abstract: Despite evidence that the restoration of apical support is important for optimal anterior support, the overall rate of concomitant apical suspensory procedures is low. Several factors may play a role in whether or not women receive an apical suspensory procedure. This study highlights opportunities to improve the quality of surgical care provided to women with anterior vaginal prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…These codes are generated by coding personnel, not the surgeon, which can lead to misclassification and transcription errors. 32 As ICD-9 codes are primarily used for hospital billing, this data may not adequately capture the true extent of procedures performed. However, since the codes are used for hospital billing, if a diagnosis or procedure is described in the medical record it is likely to be listed as part of that patient’s hospitalization and/or surgery.…”
Section: Commentmentioning
confidence: 99%
“…These codes are generated by coding personnel, not the surgeon, which can lead to misclassification and transcription errors. 32 As ICD-9 codes are primarily used for hospital billing, this data may not adequately capture the true extent of procedures performed. However, since the codes are used for hospital billing, if a diagnosis or procedure is described in the medical record it is likely to be listed as part of that patient’s hospitalization and/or surgery.…”
Section: Commentmentioning
confidence: 99%
“…Likewise, in a review of the National Hospital Discharge survey from 1979 to 2009, Stewart and colleagues found that, although there was a significant decrease in the frequency of isolated cystocele/rectocele repair procedures performed for pelvic organ prolapse, 87% of all anterior, apical, and posterior compartment prolapses were still being managed with cystocele/rectocele repair alone 16. Northington et al identified women undergoing prolapse surgery with a primary diagnosis of cystocele in 2011 from the Nationwide Inpatient Sample 17. Only 32% of these women underwent a concomitant apical prolapse procedure, suggesting an ongoing discrepancy between evidence-based medicine and adoption into clinical practice 17.…”
Section: All About the Apexmentioning
confidence: 99%
“…Northington et al identified women undergoing prolapse surgery with a primary diagnosis of cystocele in 2011 from the Nationwide Inpatient Sample 17. Only 32% of these women underwent a concomitant apical prolapse procedure, suggesting an ongoing discrepancy between evidence-based medicine and adoption into clinical practice 17. These data are concerning given that an unacceptably high number (17%) of women who underwent a procedure for POP will undergo a second surgery for recurrent POP within 10 years 18…”
Section: All About the Apexmentioning
confidence: 99%
“…Może dojść do zmiany ułożenia macicy i pochwy, czemu często towarzyszy obniżenie dolnych dróg moczowych -zwykle przebiegające z objawami klinicznymi, a w krańcowych stanach prowadzące do wypadania macicy i pochwy oraz znacznych zaburzeń w oddawaniu moczu. Czynnikiem zaburzającym ekosystem pochwy i wpływającym na atrofię jej ścian jest przebyte leczenie napromienianiem (brachyterapia) z powodu nowotworów macicy (szyjki i endometrium) (9)(10)(11) . Istnieją różne systemy klasyfikacji omawianych zaburzeńoparte na ich liczbie i nasileniu oraz na objawach klinicznych (1,(12)(13)(14) .…”
unclassified
“…Sposób leczenia obniżenia przedniej ściany pochwy i nietrzymania moczu zależy od nasilenia objawów, dolegliwości klinicznych, stanu zdrowia kobiety oraz jej oczekiwań i decyzji -zwłaszcza pacjentki, które przebyły leczenie z powodu raka endometrium, nie chciały poddać się operacji, laseroterapii (lasery Er:YAG, CO 2 ) czy zakładaniu pessarów (1,9,19) . Stosuje się wiele metod, w tym klasyczne leczenie operacyjne, wszczepianie różnych siatek lub taśm syntetycznych, techniki stymulacji laserowej i środki farmakolo giczne (6,11,(19)(20)(21) . Do sposobów leczenia cystocele i wysiłko wego nietrzymania moczu należą terapia fizyczna polegająca na ćwiczeniu mięśni miednicy (ćwiczenia Kegla), dopochwowe stosowanie pessarów lub estrogenów i zmiana stylu życia (6,16,22,23) .…”
unclassified